Contribution of the class tutor to the relation school-family - Alho, Susana Maria da Silva Pereira (2009)
It is our intention with this article to disseminate the results of the study implemented in a basic school. It was our concern to make charts that express the results of the instruments applied to teachers, students and parents, and the analysis we processed in them in order to understand the steps the class tutor took in order to know better the students’ families. The class tutor can contribute to a better relation between school and family through private meeting, reunions with education authorities and inquiries with the students, all three strategies seem to have good results.